Simulator Pesawat Melewati VHF Omnidirectional Radio Range (VOR) - Ariawan D. Rachmanto; Iswanto (FTK UNSURYA, 2020)
Commercial airplane flights always follow the flight plan that was made, the flight plan was made by the pilot based on the existing airways. Airways connects airports with VOR/DME, where VOR/DME in flight are known as air navigation equipment. VOR/DME is needed by a pilot so that he does not lose direction so that the aircraft can fly to the destination airport. The HSI instrument provides visualization of bearing, course, from to and destination VOR/DME deviations. Information from HSI is information that the pilot uses to get to the next VOR/DME. The purpose of this research is to make an aircraft movement simulation software approaching VOR, a software development method using the Prototype model by looking at existing devices. Simulation and modeling are done by placing VOR/DME at latitude and longitude in accordance with the location on land, then modeling the location of VOR/DME using MapX4.5 map, air conditioned flight at the specified airport, HSI instrument is modeled using GL Studio, using language C # programming, Indonesian VOR/DME data and Indonesian airports are stored in Excel. The calculation results are then visualized on the HSI instrument, the instrument visualization results are compared with the Garmin Integrated Flight Deck (GIFD) Trainer, version 14.01 under the same conditions.